The Effect of Using End-to-End Encryption in Improving Data Security in Cloud Computing - Satya Arisena Hendrawan; Legito; Muhammad Bitrayoga; Jatmiko Wahyu Nugroho; Arnes Yuli Vandika (Universitas Muhammadiyah Palu, 2025)
Cloud Computing offers various advantages, but also presents major challenges related to data security. End-to-end encryption (E2EE) is considered as a solution to mitigate threats to the security of data stored and processed in the cloud. This research aims to examine the effect of implementing E2EE encryption in improving data security in Cloud Computing. Using a qualitative approach with literature study and secondary data analysis, this research focuses on three main threat categories: data leakage, unauthorized access, and cyberattacks. The results show that E2EE encryption can reduce the incidence of data leakage by 80%, unauthorized access by 83.3%, and cyberattacks by 78.6%. Despite its effectiveness, E2EE encryption implementation faces challenges in encryption key management and potential degradation in system performance. Therefore, good key management and multifactor authentication are essential to ensure data security. This study concludes that although end-to-end encryption improves security, a thorough policy, including key management and access control, is needed to maximize data protection in Cloud Computing.